Comparison Of Growth And Reproductive Responses Of Calves To An Intratesticular Injection Of Zinc Tannate And Castration - Mohammad, Nihayah (1992)

(untitled)
A study was carried out to demonstrate that intratesticular injection of 6% zinc tannate to indigenous Kedah-Kelantan (KK) calves will result in better growth rates and superior carcass characteristics than calves castrated with burdizzo and that it would selectively destroy the spermatogenic cells and not the interstitial cells ( Leydig cells) . Thirty KK male calves aged 9 - 10 months old were selected and assigned to three treatment groups with 10 animal sin each group . Animal sin group 1 were castrated with a burdizzo(BC) , group 2 animals were injected intratesticularly with 6% zinc tannate (ZT ) and intact animals in group 3 as a control group (CT ) . The dose o f 6% zinc tannate injected was based on scrotal circumference . All the animals were slaughtered after 368 days post-treatment .There was no significant difference ( P >0 . 05 ) in average daily weight gain of animals injected with zinc tannate (0.38±0.007 kg ) , castrated ( 0.34±0.07 kg ) and intact (0.43 ± 0.007 kg ) animals; but intact animals showed higher ( P<0.05 ) gain than the castrated animals. Zinc tannate animals had lower daily feed intake and better feed conversion ratio than castrated and intact animals . No significant differences were observed in chilled dressing percent , muscle and bone percent and muscle : bone ratio of the three treatment groups but a higher percentage of f at was found in castrated animals . This study revealed that zinc tannate is an irreversible chemical sterilant . Histological section of testes indicated complete destruction of spermatogenic cells with intact Leydig cells in the interstitium . No spermatozoa were observed in the ejaculates and the animals produced high levels o f testosterone hormone . It is concluded that zinc tannate could be used as a substitute for burdizzo cast ration and as an alternate procedure for the preparation o f teaser bulls.